If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + -1(-10) = 2 Multiply -1 * -10 s + 10 = 2 Reorder the terms: 10 + s = 2 Solving 10 + s = 2 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + s = 2 + -10 Combine like terms: 10 + -10 = 0 0 + s = 2 + -10 s = 2 + -10 Combine like terms: 2 + -10 = -8 s = -8 Simplifying s = -8
| 24=60-x | | 3x+12=6x+5 | | 4=16-n | | 4(2x+4)-13= | | 5x^3+21x^2-21x+5=0 | | 5(n+8)=10 | | 5x^2-5x-30=30 | | 50t+125=30t+200 | | 5x-x+4x=7-3 | | x+2.75=6 | | 7x-4=6.5 | | 9-6x=4-3x+3x | | 4-2x=14x+15 | | 2t+6=t+8 | | 0.5sin(2x)=cos(x) | | 3(x-2)=2x+16 | | 14=12-10y | | 4(w-9)=6w-38 | | -5n-8(1+n)=-8 | | -16-4y=46 | | 2x^2+20x=22 | | 49x-64x^2=0 | | x^2+0.5x=0.25 | | -8x+13=-3(x-6) | | x^2-0.5x-0.25=0 | | x^2+0.5x-0.25=0 | | -3y-2(-7+5x)=12 | | x^2+0.5x-2.5=0 | | 9y-5(y+2)-3= | | 65x+10=55x-100 | | -3x-2(-7+5y)=12 | | 56X^2-103X+45=0 |